Fibrosis-4 Index vs Nonalcoholic Fatty Liver Disease Fibrosis Score in Identifying Advanced Fibrosis in Subjects With Nonalcoholic Fatty Liver Disease: A Meta-Analysis - Castellana, Marco; Donghia, Rossella; Guerra, Vito; Procino, Filippo; Castellana, Fabio; Zupo, Roberta; Lampignano, Luisa; Sardone, Rodolfo; De Pergola, Giovanni; Romanelli, Francesco; Trimboli, Pierpaolo; Giannelli, Gianluigi (The American journal of gastroenterology, 2021)
In subjects with nonalcoholic fatty liver disease (NAFLD), advanced fibrosis (AF) carries the highest risk of adverse liver-related events. To reduce the number of unnecessary biopsies, several noninvasive tools (NITs) for the risk stratification of fibrosis have been developed. We conducted this meta-analysis to assess the performance of the fibrosis-4 index (FIB-4) and NAFLD fibrosis scores (NFS), the 2 most common NITs, for the appropriate selection of subjects with AF for biopsy. Four databases were searched until December 2020 (CRD42021224766). Original articles reporting data on the performance of FIB-4 and NFS, interpreted according to standard cutoffs in subjects with biopsy-proven NAFLD, were included. Separate data extractions were performed according to the lower cutoff, the higher cutoff, and the dual threshold approach. The numbers of subjects classified as true-negative, true-positive, false-negative, and false-positive were extracted. Summary operating points were estimated using a random-effects model. Eighteen studies evaluating 12,604 subjects were included. Participants were adult outpatients with biopsy-proven NAFLD or nonalcoholic steatohepatitis. Overall, a weak-to-moderate performance was found for both scores. The head-to-head comparison showed FIB-4 to be associated with a higher performance in ruling in and NFS in ruling out AF in the single threshold approach, whereas, with the dual threshold approach, a lower prevalence of indeterminate findings was found for FIB-4. This meta-analysis suggested that currently available NITs have a limited performance in identifying AF among subjects with NAFLD. Further studies are needed to optimize existing thresholds or develop new NITs.